The Change in the Expectations of Polish Young Adults towards the Offer of Online Stores - Leszek GRACZ (Communications of International Proceedings, 2021)
Objective – The objective of the paper is to examine the change between the expectations of Polish young adults towards the offer of online stores in the years 2012-2020, in the scope of the frequency of shopping on the internet, reasons for shopping on the internet and factors related to the offer of online stores that may induce young adults to start purchasing or purchasing more frequently online. Methodology – Two surveys using CAWI method were conducted in 2012 and 2020. A total of 770 respondents (young adults) participated in the research in 2012. The study in 2020 was conducted on a group of 1115 respondents, out of which 281 were young adults. The model of online purchasing process was elaborated using the classical buyer decision process, highlighting the decisions factors. Findings – between the years 2012-2020 Polish young adults intensified their online purchases. In 2020 Polish young adults are much more aware of various aspects of online purchasing - there has been a significant growth of importance in every factor influencing online purchases. The most often indicated factors for choosing an online store are low product prices, quick order fulfillment, instant product availability, selection of various payment methods and low delivery costs. Among the reasons for online purchasing, the convenience and time saving was most important one. The reasons that remain very important are lower prices and a wide selection of products on the internet. Originality/value – The paper is based on two research studies allowing to capture the change in the behavior of the Polish Young Adults. The paper uses author's own methods of classifying factors influencing online purchases.
Keywords: Online Shopping; Online Consumer Behavior; Young Adults; Online Buyers Expectations